UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN LENGKUAS (Alpinia galanga L.) TERHADAP Escherichia coli - Putri Ema Hartanty; Na’imatul Retno Faizah; Octaviana Dyah Oentari (PT. Saha Kreasi Indonesia, 2025)
Diarrhea is caused by bacteria, one of which is Escherichia coli, which is still a serious health problem, especially due to increasing resistance to synthetic antibiotics. Efforts are being made to overcome this by looking for natural antibacterial agents from medicinal plants, one of which is galangal leaves (Alpinia galanga L.). This study aims to evaluate the antibacterial activity of ethanol extract of galangal leaves against Escherichia coli. This research used a true experimental method with concentration variations of 5%, 10% and 20%. The antibiotic ciprofloxacin was used as a positive control, and distilled water as a negative control. Galangal leaves were extracted using the maceration method with 70% ethanol solvent, and the antibacterial test was carried out using the disk disk method. Data analysis was carried out using one way ANOVA. The results showed that the ethanol extract of galangal leaves had significant antibacterial activity, with an average inhibition zone diameter of 13.72 mm (5%), 14.39 mm (10%), and 15.38 mm (20%). The results of all data were normally and homogeneously distributed with values > 0.05 and the ANOVA test results were 0.00 (p<0.05) which indicated there were significant differences between concentrations. Based on the classification of inhibitory power, antibacterial activity at a concentration of 20% is included in the strong category. This research indicates that the ethanol extract of galangal leaves has the potential to be a natural antibacterial agent against Escherichia coli.